2014
DOI: 10.1136/emermed-2013-203382
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of clinical practices to reduce return visits within 72 h to a paediatric emergency department

Abstract: The development and implementation of clinical practices were effective in reducing return visits of paediatric patients to the ED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…We did not find differences, probably due to the sample size not being calculated for this outcome: in order to find a difference between 25 and 15% rates of return visits, we would have needed to randomize 464 patients, more than three times more the sample size we used for our primary outcome. A previous before-and-after study [21] found that implementing a set of clinical practices which included standardized (but not video) instructions would reduce subsequent visits to PED. However, this study included more measures such as identification of risk factors, management plans, feedback systems, and planned visits to clinics.…”
Section: Discussionmentioning
confidence: 98%
“…We did not find differences, probably due to the sample size not being calculated for this outcome: in order to find a difference between 25 and 15% rates of return visits, we would have needed to randomize 464 patients, more than three times more the sample size we used for our primary outcome. A previous before-and-after study [21] found that implementing a set of clinical practices which included standardized (but not video) instructions would reduce subsequent visits to PED. However, this study included more measures such as identification of risk factors, management plans, feedback systems, and planned visits to clinics.…”
Section: Discussionmentioning
confidence: 98%
“…Measuring paediatric re‐attendances that do require admission may be a better measure. Improvement work has been described with respect to this measure, with caution raised regarding the use of physician review to identify improvement opportunities and reductions in re‐attendance achieved by patient flow improvements …”
Section: Effectiveness and Efficiencymentioning
confidence: 99%
“…5,6 Discharge instruction complexity and inadequate comprehension is associated with medication errors, suboptimal postdischarge care, and unnecessary recidivism. [7][8][9][10] Medication errors can be reduced using standardized discharge instructions, and parents prefer these to verbal summaries. [11][12][13] Video discharge instructions have been shown to be preferred over paper instructions in many pediatric presentations; however, no study has explored the effectiveness of video instructions for AOM.…”
Section: Introductionmentioning
confidence: 99%